ANALISIS STRATEGI DISTRIBUSI KONTEN WEBSITE HELLOSHABBY.COM MELALUI FACEBOOK DALAM MENINGKATKAN TRAFFIC GLOBAL - Nurkamit; Denis Fidita Karya (J-MACC, 2026)
This study aims to analyze the content distribution strategy of Helloshabby.com through Facebook in increasing global website traffic. The research employs a descriptive qualitative approach with data collection techniques including observation, documentation, and website statistical data analysis. The study focuses on Facebook’s role as a content distribution channel, its contribution to website traffic growth, and the resulting global audience reach. The findings reveal that Helloshabby.com generated a total of 886,000 views within a three-month period, with Facebook ecosystem referrals contributing approximately 155,000 visits, or around 17.5% of total traffic, significantly higher than Google’s contribution of 36,600 visits. Furthermore, global visitor data indicates that the website audience is dominated by several countries, including the Philippines (141,000), the United States (123,000), Singapore (37,000), and Hong Kong (36,200). These findings suggest that Facebook-based content distribution is effective in expanding international audience reach, increasing website visibility, and driving social media-based traffic. Therefore, Facebook is proven to function as a strategic distribution channel in supporting the growth of global traffic for Helloshabby.com.